Historical and cultural perspectives of pigs in ancient India and prospects of natural pig farming in contemporary India - R THOMAS; V K GUPTA; V K VIDYARTHI; R SOMVANSHI; N M ATTUPURAM; S KUMAR; R K SINGH (Indian Journal of Animal Sciences, 2025)
The mythology and ancient history of India reveal that the pig held great cultural and civilizational significance. The intriguing symbolism that a boar represented in our history can be discovered through a cultural revisit through the sculptures and inscriptions. The pig was also portrayed as a symbol of prosperity in ancient Indian agriculture. The domestication of pigs, Sus scrofa domesticus, has deeply impacted human societies across the globe, contributing to food security, agricultural practices, and cultural diversity. The current pig population in India is 9.06 million in comparison to the world population of about 778 million. Out of total pig population, 79.03 percent are indigenous and non-descript in India which make them well suited for natural farming. Current world pork production stand at 112.6 million tons, which has been estimated to grow at the pace of 2.3 percent year to year and expected to rise to 129 million tons by 2031.The world market for organic pork is a niche has been rapidly expanding segment within the global meat industry. At present pork is one of the most traded products in the world that held 136th position in 2022. India exported $3.75M and imported $2.97M pork in the year 2022, making it the 46th among the exporter and112th among importer of pork in the world. There is no doubt that natural and sustainable pig farming, combined with value addition and carbon neutrality, will greatly increase the prospects for Indian pig sector.